Strengthening Good Governance as an Entry Point for Eradicating Corruption During the Covid-19 Pandemic - Purnaweni, Hartuti; Widianto, Dhoni; Qomariah, Anis; Suharso, Pudjo (KnE Social Sciences, 2022)
In 2015, the Corruption Perception Index (CPI) Report ranked Indonesia 107th out of 180 countries surveyed, and Transparency.org ranked Indonesia 89th out of 180 countries surveyed. Many studies have been conducted on corruption in Indonesia, but few articles have linked corruption to good governance for development in the country. Corruption can be addressed by strengthening good governance as a starting point for eradicating corruption, followed by anticorruption policy reform. The goal of this research was to look at corruption cases in Indonesia through the lens of good governance. This study was a policy-oriented study using a literature search of journal articles on corruption, with data from a variety of sources including the Indonesia Corruption Watch, Corruption Eradication Corruption (KPK), World Bank, and Transparency International. Focus group discussions were also conducted. The Spradley model was used in the data analysis through domain analysis, componential analysis, and theme analysis. The outcomes demonstrated that corruption is a unique crime that is difficult to eradicate. As a result, since good governance is not widely practiced in Indonesia, it must be emphasized. Strengthening good governance is recommended as a key to eradicating corruption in Indonesia, such as by strengthening law enforcement with the law structure as an example. Keywords: corruption, policy, good governance, policy reform